Determinants of visit intention: The role of city branding, tourism events, and city image in Banyuwangi, Indonesia - Della Putri Arditya; Mochammad Riyadh Rizky Adam (PT. Cendekia Sapta Indonesia, 2026)
Purpose ― This study examines the determinants of tourists’ visit intention by analysing the roles of city branding, tourism events, and city image in the context of Banyuwangi, Indonesia. Drawing on perspectives from Tourism Marketing and Consumer Behavior, the research proposes a model in which city branding and tourism events influence visit intention both directly and indirectly through city image. Methods ― A quantitative approach was employed using survey data collected from [n = 220] respondents. Data were analysed using CB-SEM with Amos. Findings ― The findings reveal that city branding and tourism events significantly affect city image, which in turn plays a crucial role in shaping the decision to visit. Furthermore, city image mediates the relationship between marketing stimuli and tourists’ behavioral intentions. Implication ― The study contributes to the literature on Place Branding by providing empirical evidence from an emerging tourism destination. Managerial implications suggest that local governments should strategically integrate branding initiatives with event-based tourism to strengthen destination image and attract visitors. Originality ― This study contributes to the literature by integrating city branding, tourism events, and city image into a unified model to explain tourists’ visit decisions. It further highlights the mediating role of city image in an emerging destination context, providing empirical evidence from Banyuwangi, Indonesia